2003
DOI: 10.1111/j.1523-1747.2003.12637.x
|View full text |Cite
|
Sign up to set email alerts
|

Collagen of Chronically Inflamed Skin Is Over-Modified and Upregulates Secretion of Matrix Metalloproteinase 2 and Matrix-Degrading Enzymes by Endothelial Cells and Fibroblasts

Abstract: In order to investigate the properties of collagen in chronically inflamed tissue, we isolated collagen from the ear skin of mice with chronic contact dermatitis and examined its biochemical characteristics and the functions that regulate the secretion of matrix metalloproteinase 2 and collagen-degrading enzymes from endothelial cells and fibroblasts. Collagen in skin with chronic contact dermatitis comprised 60% type I collagen and 40% type III collagen, which latter is higher than the content of type III col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In addition, HTS cell modification of collagen causes resistance to enzymatic cleavage by MMP-2, a collagenase highly active during cutaneous wound healing. These results are analogous to recent findings in a model of chronic dermatitis induced in rabbit ears (Hirota et al, 2003) and are of particular interest considering work by Buckley et al (1999), who implicated potential breakdown products of the ECM in the initiation of apoptosis in both lymphocytic cells and fibroblasts. Small soluble peptides containing the RGD amino acid motif were reported to directly induce apoptosis through an integrinindependent mechanism by direct binding to and activation of pro-caspase-3 as apposed to the alternative mechanism of inducing apoptosis (termed anoikis) through blocking integrin-mediated cell-matrix contact (Frisch and Ruoslahti, 1997).…”
Section: Figuresupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, HTS cell modification of collagen causes resistance to enzymatic cleavage by MMP-2, a collagenase highly active during cutaneous wound healing. These results are analogous to recent findings in a model of chronic dermatitis induced in rabbit ears (Hirota et al, 2003) and are of particular interest considering work by Buckley et al (1999), who implicated potential breakdown products of the ECM in the initiation of apoptosis in both lymphocytic cells and fibroblasts. Small soluble peptides containing the RGD amino acid motif were reported to directly induce apoptosis through an integrinindependent mechanism by direct binding to and activation of pro-caspase-3 as apposed to the alternative mechanism of inducing apoptosis (termed anoikis) through blocking integrin-mediated cell-matrix contact (Frisch and Ruoslahti, 1997).…”
Section: Figuresupporting
confidence: 87%
“…We further postulated that this phenomenon of apoptotic resistance might be caused by the matrix of HTS being overmodified in some way, either via intracellular posttranslational modification that goes on during biosynthesis or through extracellular biochemical modification, since chronic fibrotic tissue (both skin and liver) is known to be excessively cross-linked (Ricard-Blum et al, 1993, 1996Dolynchuk, 1996;Hirota et al, 2003). Overmodification of ECM would considerably change its biochemical properties and how cells interact with it, potentially affecting the mechanical properties of the matrix and thus the tensional load put upon the inhabiting cells.…”
Section: Figurementioning
confidence: 98%
See 1 more Smart Citation
“…ACD involves deformation of cutis and epidermis texture as well as remodeling of collagen fibre streaks. An increased amount of type I and type III collagen has been demonstrated in the skin affected by chronic contact dermatitis [ 28 ]. Fibroblasts are among potential targets of MMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its structural role, skin ECM plays a physiological role, by influencing the immediate microenvironment of the cells embedded within it. Histological studies have reported extensive remodeling of skin ECM during growth and development (120) as well as under various pathological conditions (121,122,123).…”
Section: Strategies For the Proliferation And Terminal Differentiatiomentioning
confidence: 99%